JAN SOKOL'S APPROACH TO THE RENEWAL OF MONUMENTS WITH AN EMPHASIS ON HIS ACTIVITIES AT PRAGUE CASTLE - Martin Šnorbert (Civil Engineering Journal, 2021)
This contribution deals with the approach of the architect Jan Sokol to the renovation of monuments within his architectural work. Close attention is paid to the biographical part, as it describes the development of the architect's relation to the history of art and cultural heritage of previous generations. Personalities who influenced him during his studies, but also during architectural practice, are mentioned. It also captures the period when Sokol worked as an employee in a state studio which was focused on the preservation and restoration of monuments. Subsequently, selected buildings and projects designed by this architect in the field of historic preservation are discussed. Of these, the most emphasized are the projects which were created for the area of Prague Castle. To understand these projects, the preserved texts, plans and ideas of the author are used. Unfortunately, many of the discussed projects were not implemented, but they are very valuable in their thought form. And this is one of the reasons why this article iss written, it tries to show the quality of Sokol's projects. Furthermore, the purpose is to point out the personality of the architect, who has not been fully appreciated yet, nevertheless he has inspired several of his students and other architects. In conclusion, it is pointed out that the Sokol's discussed approach was based on a deep knowledge of the construction of the historical buildings and history of art, and that led him to approach to these buildings with a certain humbleness. It is further stated that the architect Jan Sokol was a generally gifted author with an overlap into fields areas.